Desenvolvimento de candidatos a fármacos para tratamento da Leucemia Mielóide Crônica a partir do Imatinibe - SANCHES, Vitor Hugo da SIlva (Universidade Federal do Pará, 2022)
Chronic Myeloid Leukemia (CML) is a chronic clonal myeloproliferative disease, characterized by leukocytosis with left shift, splenomegaly and the presence of the Philadelphia (Ph) chromosome, which results from the reciprocal and balanced translocation between the advanced states of chromosomes 9q34 and 22q11, generating a hybrid protein BCR-ABL, with increased activity of tyrosine kinase. Thus, it carried out a virtual screening study based on the ligand Imatinib, with a defined crystallographic pose, deposited under the code PDB ID 1IEP. Six databases of merchants were used to select molecules, using the software ROCS (shape similarity) and EON (electrostatic similarity), followed by pharmacokinetic and toxicological predictions in silicon, resulting in 9 methods with satisfactory values, compared with Imatinib , which were submitted to a study of biological activity prediction via PASS Prediction online server, resulting in two structures with Probability of being "active" (Pa) values for protein kinase inhibition activity, such as LMQC01 molecules (Pa = 0.457) and LMQC04 (Pa = 0.658), selected for the study of molecular docking. Use a Pyrx 0.8 graphical interface, to evaluate as likely interactions with amino acid residues and binding affinity as structures with the BCR-ABL active site, resulting in -8.6Kcal / mol-1 for structure LMQC01 and -12.2Kcal / mol -1 for LMQC04, with the LMQC04 structure reaching a value higher than the experimental binding affinity of imatinib (-11.18Kcal / mol-1), being the one selected as a drug promoter for further studies.